2021
DOI: 10.1515/jom-2021-0103
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein levels associated with COVID-19 outcomes in the United States

Abstract: Context COVID-19 caused a worldwide pandemic, and there are still many uncertainties about the disease. C-reactive protein (CRP) levels could be utilized as a prognosticator for disease severity in COVID-19 patients. Objectives This study aims to determine whether CRP levels are correlated with COVID-19 patient outcomes and length of stay (LoS). Methods A ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 7 publications
2
14
0
Order By: Relevance
“…In our study, CRP was found to be marginally associated with mortality in patients with COVID-19 with an OR of 1.01. This was similar to what was found in 2 other studies where CRP had an OR of 1.007 (95% CI = 1.004–1.010, p = 0.0001 and 95% CI = 1.005–1.009, p < 0.001) ( 45 , 46 ).…”
Section: Discussionsupporting
confidence: 91%
“…In our study, CRP was found to be marginally associated with mortality in patients with COVID-19 with an OR of 1.01. This was similar to what was found in 2 other studies where CRP had an OR of 1.007 (95% CI = 1.004–1.010, p = 0.0001 and 95% CI = 1.005–1.009, p < 0.001) ( 45 , 46 ).…”
Section: Discussionsupporting
confidence: 91%
“…Most indicators match for these two graphs, which demonstrates the stability and significance of the discovered relationships in the two graphs. The graph in Figure 6 shows a link between the length of stay and C-reactive protein (its link with COVID-19 outcome has been proven in many studies [ 36 ]) on the one hand and PLT (which influences COVID-19-related length of stay as described in [ 37 ]) on the other hand.…”
Section: Resultsmentioning
confidence: 79%
“…In this study 56% of patient had comorbidities for covid 19 such as hypertension, diabetes, ischemic heart disease, chronic kidney and liver disease .COVID-19 patients with pre-existing comorbidities had a higher likelihood of death. These findings could potentially help doctors to sort out the most susceptible COVID-19 patients by comorbidities, take precautionary measures which could potentially reduce the number of fatalities in COVID-19 (20) .In the early stage of COVID-19 CRP levels were positively correlated with lung lesions and could reflect disease severity (21) and there is a positive correlation between the CRP levels of COVID-19 patients and their respective outcomes with regard to death (22). High CRP levels in COVID-19 patients are strongly associated with the prognosis of COVID-19 which must be employed within the clinical practice to guide COVID-19 disease severity (23) .A recent study showed that about 7.7% of non-severe COVID-19 patients were progressed to severe disease courses after hospitalization (24) .In this study when we investigated the effect of initial crp level on severity and complication and prognosis of patients with laboratory-confirmed COVID-19 and we found that found that CRP levels are predictive factor of complication development ,and independent of factors such as gender ,severity and comorbidities ,CRP increase in complicated patients with COVID 19 infection (p value 0.018)which is significant.…”
Section: Discussionmentioning
confidence: 89%